EXPLORING THE ROLE OF TRAINING OF TRAINERS PROGRAMS IN PREPARING ENGLISH LANGUAGE TEACHERS FOR AI INTEGRATION (Contemporary Journal of Social Science Review, 2025)
The rapid advancement of Artificial Intelligence (AI) in education has created new opportunities and challenges for English language teaching. While AI-driven tools offer innovative ways to enhance learning experiences, their effective use depends largely on teachers’ preparedness and confidence in integrating them into classroom practice. This study explores the role of Training of Trainers (ToT) programs in preparing English language teachers for AI integration. Using a qualitative research design, data were collected through semi-structured interviews and focus group discussions with trainers and teacher participants involved in AI-focused ToT initiatives. Thematic analysis was employed to examine participants’ perceptions, experiences, and challenges in adopting AI for pedagogical purposes. Findings reveal that ToT programs serve as a critical bridge between technological innovation and classroom application by equipping teacher educators with both technical knowledge and pedagogical strategies. Participants highlighted the importance of practical demonstrations, collaborative learning, and continuous mentoring in building AI literacy. However, challenges such as limited access to resources, varying levels of digital competence, and resistance to change emerged as barriers. Despite these constraints, the study found that ToT programs fostered a supportive professional community that encouraged experimentation and innovation in teaching practices. The research underscores the need for sustained and context-sensitive ToT models that go beyond technical training to address pedagogical integration and reflective practice. Ultimately, the study contributes to understanding how professional development structures can empower English language teachers to harness AI effectively, enhancing both teacher agency and student learning outcomes.